Complete genome sequence data describing the biosynthetic potential of kanosamine and bacilysin in Bacillus subtilis AMFE023/7 from Thai fermented fish (Pla Ra)Original data - Montri Yasawong; Thunwarat Songngamsuk; Manassanan Phatcharaharikarn; Parweenuch Santaweesuk; Prapimpun Wongchitrat; Prasit Palittapongarnpim; Wongwarut Boonyanugomol; Arunee Thong-on; Sasalux Kaewbutra; Kamolchanok Rukseree (Data in Brief)
Bacillus subtilis AMFE023/7, a Gram-positive bacterium with aciditolerans and halotolerant properties, was isolated from Pla Ra, a traditional fermented fish product popular in Thai cuisine. The sample was obtained from a local morning market in Amnat Charoen, Thailand. The complete genome was assembled through the integration of complementary sequencing platforms, specifically Illumina and PacBio. The genome spans 4132,147 base pairs with a GC content of 43.87 %. Comparison with the reference strain B. subtilis ATCC 6051T using digital DNA-DNA hybridisation confirmed the identity of the isolate with 89.3 % similarity. The genome analysis revealed gene clusters responsible for producing potentially useful compounds such as kanosamine and bacilysin, which have antimicrobial properties. This genome sequence provides valuable data for researchers studying microbial communities in fermented foods, those conducting comparative genomics, and scientists searching for new bioactive compounds. The complete genome sequence data has been made publicly available through NCBI under BioProject accession number PRJNA1253417.